DAKWAH DAN PERDEBATAN SOAL PLURALISME - Thaib, Erwin Jusuf; Kango, Andries (KOMUNIKE, 2020)
Da'wah is basically a social activity that allows people to meet with various social backgrounds in it. Because of its nature as a social activity, plurality becomes a necessity in da'wah. Nevertheless, pluralism as a reality sometimes becomes a problem in society. This article aims to describe the problem between da'wah and pluralism with the subject of the meaning of pluralism, its reality in the history of Islamic da'wah, and the attitude that must be developed in responding to it. The study showed that pluralism is generally interpreted as diversity in various aspects of life, including religion, which is believed to originate from one source even though this causes controversy. Historically Islam recognized the reality of religious pluralism. This fact shows that in Islam differences of belief are not obstacles to managing social life together as a form of acceptance of religious pluralism. Some attitudes that must be developed to be able to accept the reality of religious pluralism in daily life include interfaith dialogue, conducting "passing over" and "coming back" activities, or making efforts to increase multiculturalism insight to all elements of society. All of this can be done through the Islamic da’wah, with its various approaches, has become a massive Islamic religious social movement and is able to reach all aspects of Islamic society life.